2019
DOI: 10.7554/elife.46574
|View full text |Cite
|
Sign up to set email alerts
|

Structural mapping of oligomeric intermediates in an amyloid assembly pathway

Abstract: Transient oligomers are commonly formed in the early stages of amyloid assembly. Determining the structure(s) of these species and defining their role(s) in assembly is key to devising new routes to control disease. Here, using a combination of chemical kinetics, NMR spectroscopy and other biophysical methods, we identify and structurally characterize the oligomers required for amyloid assembly of the protein ΔN6, a truncation variant of human β2-microglobulin (β2m) found in amyloid deposits in the joints of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
98
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(104 citation statements)
references
References 90 publications
(162 reference statements)
5
98
1
Order By: Relevance
“…In these types of experiments at low monomer concentrations, linear behaviour of the growth rate, as a function of the monomer concentration, is usually found, in agreement with the idea that fibril growth is a bimolecular reaction between a monomer and a fibril end [37,39,48,49]. Indeed, if amyloid fibrils were to grow by the addition of dimers or larger oligomers in equilibrium with monomers, a higher than linear dependence of the growth rate on the concentration of soluble protein can be expected, as has recently been reported for the first time in the case of the ΔN6 variant of β2microglobulin [50]. Therefore, a careful examination of the concentration dependence of amyloid fibril growth rates at low concentration allows us to define the elongating species.…”
Section: The Concentration-dependence Of Amyloid Fibril Growthsupporting
confidence: 83%
“…In these types of experiments at low monomer concentrations, linear behaviour of the growth rate, as a function of the monomer concentration, is usually found, in agreement with the idea that fibril growth is a bimolecular reaction between a monomer and a fibril end [37,39,48,49]. Indeed, if amyloid fibrils were to grow by the addition of dimers or larger oligomers in equilibrium with monomers, a higher than linear dependence of the growth rate on the concentration of soluble protein can be expected, as has recently been reported for the first time in the case of the ΔN6 variant of β2microglobulin [50]. Therefore, a careful examination of the concentration dependence of amyloid fibril growth rates at low concentration allows us to define the elongating species.…”
Section: The Concentration-dependence Of Amyloid Fibril Growthsupporting
confidence: 83%
“…A recent study that combined NMR and MD simulations reported that the formation of hexamers by the association of dimers is an essential step in the aggregation pathway of the ΔN6 variant ( Karamanos et al, 2019 ). The inter-dimer interfaces comprise the ABED β-sheet and the BC, DE, and FG loops, while the intra-dimer interfaces is formed by the N-terminal A strand, and the BC, DE, and FG loops.…”
Section: Early Phase Of β2m Aggregationmentioning
confidence: 99%
“…The amyloidogenic variant of β2m which is the focus of this paper -ΔN6is formed from the wild-type protein by proteolysis of its N-terminal six amino acids and makes up ~20-30% of β2m molecules found in fibrils extracted from DRA patients 34,35 . ΔΝ6 is capable of rapid assembly into amyloid fibrils in vitro at near-neutral pH, through the association of the dynamically-structured monomers 36 into dimers and hexamers that retain a native-like fold 37 ( Figure 1A). Subsequent conformational rearrangement of these oligomers into cross-β structures leads to amyloid fibril formation and elongation 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent structural models of ΔN6 dimers and hexamers have shown that the DE and BC loops of the protein are involved in both oligomerization interfaces ( Figure 1A) 37 . The same regions have also been identified at the interface of amyloid-competent ΔN6-β2m heterodimers 39 , β2m-β2m homodimers 40 , and inhibitory heterodimers formed between ΔN6 and a non-amyloidogenic β2m ortholog (murine β2m) 39 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation